(untitled) (Boletín Semillero de Investigación en Familia, 2022)
Introduction: there is a close relationship between the quality of care and the satisfaction of users to achieve the balance of the health system. The quality of health care is an issue that is becoming increasingly relevant due to the freedom with which users express opinions about the services received, those responsible for providing health services and the institutions that provide these services. Objective: to determine the satisfaction of patients with nursing care in the emergency department of a first level institution in Cúcuta, Norte de Santander, based on the NOC scale from the perspective of Katharine Kolcaba. Materials and methods: cross-sectional descriptive quantitative research. A Likert scale of NOC taxonomy criteria was used as an instrument. Results: when relating the nursing care provided in the emergency service of a first level institution with the satisfaction that users perceive when receiving such care, it is found that the variable that predominates or that most satisfies the patient’s need is relevance. since the necessary materials and personnel are available to satisfy the patient’s needs, which allows reaching an optimal state of health that is reflected in the questionnaire applied in the service under study, in which it was obtained that 83% of those interviewed are between completely satisfied and very satisfied. Conclusions: it is concluded that users who attend the emergency service of the first level institution in the city of Cúcuta are 78% very satisfied or completely satisfied with the care provided.